(untitled) (Journal of the College of Education for Women, 2023)
This study is concerned with revealing the semiotics of thresholds, and its role in building textual coherence at the form and semantic level in Sunset Garden Diwan of the Saudi poet Ghazi Al-Qasaibi. This research aims to spotlight on the semiotic theme of the title threshold and its relation to other thresholds. As the death phenomenon and absence dominated the poetic achievement space through intertwined semiotic relationships that lead to each other through the parallel text semiotics.This study is based on the semiotic method which concerns with searching for the interpretive connotations and revealing the profound symbols in the threshold structure and its role in the whole formation of the Diwan. Among the most prominent conclusions for this study is that; AlQasaibi was concerned with the thresholds poetics in his book Sunset Garden and he was able to transfer the meaning of thresholds from the margin to the centre when he revealed the significance of the symbols and connotations of the thresholds in the Diwan, which contributed to the space and coherence of the text.It also balanced between the centrality of receiving. Moreover, the poetic thresholds and their semiotic symbols contributed to the manifestation of the Diwan purposes and its contents, forming a unified texture starting with the front cover and ending with the back cover of the Diwan. The semiotic analysis of the poetic threshold in Sunset Garden Diwan showedAlQasaibi special vision of death and absence merged with nostalgia, eulogy and reconciliation with the concept and reality of death. The title also represents the first thresholds of the text that cannot be crossed.That is because it has the codes and symbols that help the reader and recipient to introspect the entire work.